TOEFL Preparation for University Students’ Candidates from Asak Paroki MKK - Clara Herlina (Bina Nusantara University, 2020)
Some private universities in Jakarta use TOEFL or TOEFL-like test as the admission requirement for new students. Therefore, students’ candidates should prepare well to achieve the minimum score for being admitted. Unfortunately, their high school did not give enough training in doing the TOEFL test. The purpose of this community development program is to train high school students to do TOEFL test, especially the Reading section. The participants of the program were seven 12th grade high school students who were included in ASAK Paroki MKK community. They were trying to qualify for admission in Binus University. The program was created in the form of classroom teaching and individual assignment. In this program, we taught them about the TOEFL Reading test types, strategies and tips for doing the test. After the training, the students reported their understanding of TOEFL and confidence in preparing the university admission test.